Therapeutic itineraries and childhood cancer in Argentina: Peripheral perspectives - Brage, Eugenia (2019)
In Argentina the attention of some childhood diseases, such as cancer, is centralized in Buenos Aires. About half of the children who fall ill with cancer must migrate to another city in search of diagnosis or medical treatment for this disease. This gives rise to different forms of territorial mobility for access to health services, topic that has not received much attention in medical anthropology. The aim of this presentation is to share the results of a doctoral research work about the therapeutic itineraries and care practices carried out by parents of children affected by cancer. The ethnographic fieldwork was carried out during May 2013 to December 2015 at a public Hospital located in Buenos Aires, as well as a non-governmental organization created to support low-income families who are suffering from this disease and, finally, a hotel where some families stay when they arrive to Buenos Aires during the period of the medical treatment and controls. The methodology consisted on observations and semi-structured interviews to child?s parents and primary carers. I will try to bring to discussion some theoretical and methodological implications about the notion of therapeutic itinerary, a category that has gained strength due to its enormous explanatory and analytical potential. Based on analyzing the reality of our health services, the work aims to expose the potential of "peripheral perspectives" (Cardoso de Oliveira, 2004) to cope with a highly changing and uneven world.